(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The article characterizes the official status and scope of the Russian language in the Republic of Uzbekistan. It is shown that the policy of strengthening the state language in modern Uzbekistan is associated with the adaptation of the late Soviet model of the nation state, in which the language was one of the most important markers of the nation. It is proved that the Russian language is one of the rooted languages of the republic. The author comes to the conclusion that the Russian language is part of modern Uzbek culture